Анализа корелације нивоа Ц1QTNF9 и Хомо-Цис у серуму са тежином лезија коронарних артерија (КХБ): Нивои серума C1QTNF9 и хомоцистеина код КХБ-а - Wang, Rui; Zhang, Man; Ran, Lafang; Tang, Guozhang; Yu, Lu (Journal of Medical Biochemistry, 2026)
[Objective] To investigate the connections between the vulnerability of coronary atherosclerotic plaques and the severity of coronary artery lesions in patients with coronary heart disease (CHD) and the serum levels of C1q/tumor necrosis factor-related protein 9 (C1QTNF9), homocysteine (Homo-Cys), and D-dimer (D-D). [Methods] Research participants were 396 individuals with suspected coronary heart disease (CHD) who came to the hospital between June 2022 and October 2025 with symptoms like tightness and pain in their chest. Through coronary angiography (CAG) examination, The CHD group consisted of 248 patients with CHD, while the control group consisted of 148 people without CHD. The two patient groups’ serum levels of C1QTNF9, Homo-Cys, and D-D were compared. Three types of CHD patients were identified based on the findings of the blood flow reserve fraction test: those with no plaque, those with stable plaque, and those with susceptible plaque. Using the Gensini scoring standards, the patients were divided into three groups according to the CAG examination results: low-risk (less than 20 points), medium-risk (20–40 points), and high-risk (more than 40 points). The patients were split into one lesion group, two lesion groups, and three or more lesion groups. Serum levels of C1QTNF9, Homo-Cys, and D-D were compared and associations were examined in CHD patients with varying coronary artery plaque stabilities, coronary artery lesion counts, and Gensini scores. [Results] The CHD group’s serum C1QTNF9 level was lower than the control group’s, despite the Homo-Cys and D-D levels being significantly greater (P<0.05). Both the stable and vulnerable plaque groups had lower serum C1QTNF9 levels than the plaque-free group, while the plaque-free group had higher levels of Homo-Cys and D-D. Furthermore, the susceptible plaque group had a lower serum level of C1QTNF9 than the stable plaque group, and the blood levels of Homo-Cys and D-D were higher than those in the stable plaque group (P<0.05). While the levels of Homo-Cys and D-D progressively increased, the serum C1QTNF9 level steadily decreased as the number of coronary artery lesion branches grew. P<0.05 indicated that these changes were statistically significant. Both the intermediate-risk and high-risk groups had lower serum C1QTNF9 levels than the low-risk group, while the low-risk group had greater levels of Homo-Cys and D-D. Additionally, the high-risk group’s serum C1QTNF9 level was lower than the intermediate-risk group’s, while the intermediate-risk group’s Homo-Cys and D-D levels were higher (P<0.05). The number of vulnerable plaques, the number of coronary artery lesions, and the Gensini score were all negatively correlated with the serum C1QTNF9 level (P<0.05), while the number of vulnerable plaques, the number of coronary artery lesions, and the serum Homo-Cys and D-D levels showed a positive correlation (P<0.05) with the Gensini score. Serum Homo-Cys was favorably connected with D-D (P<0.05), while serum C1QTNF9 was negatively correlated with Homo-Cys and D-D (P<0.05). [Conclusion] In patients with CHD, the serum C1QTNF9 level is decreased, whereas the Homo-Cys and D-D levels are increased. The serum C1QTNF9, Homo-Cys, and D-D levels are closely related to the stability of coronary atherosclerotic plaques and the severity of coronary artery lesions. Moreover, these indicators interact with each other and jointly participate in the disease progression of CHD patients.